2022
DOI: 10.1177/22799036221103108
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination perceptions and attitudes among Egyptian medical students

Abstract: Background: This study aimed to assess perceptions and attitudes toward COVID-19 vaccines among medical students. Methods: A consecutive convenient sample of 2100 university students representing the student’s union network were included using an electronic self-administered questionnaire. About 12 items were used to assess attitudes and acceptance of COVID-19 vaccines. Results: A total of 2100 volunteers responded to the survey. All ages ranged from 18 to 25 years, 69% were females, and 57.3% were from urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The results of the present study indicated that lower perception of the danger due to COVID-19 was significantly related to lower intention to obtain the vaccines. This may be due to inadequate information since Abdel-Aziz et al [ 32 ] found in their study that 66.7% of medical students did not obtain adequate information about COVID-19 vaccines. In a similar study, 68.9% of the participants were hesitant to get vaccinated due to low information about it [ 26 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The results of the present study indicated that lower perception of the danger due to COVID-19 was significantly related to lower intention to obtain the vaccines. This may be due to inadequate information since Abdel-Aziz et al [ 32 ] found in their study that 66.7% of medical students did not obtain adequate information about COVID-19 vaccines. In a similar study, 68.9% of the participants were hesitant to get vaccinated due to low information about it [ 26 ].…”
Section: Discussionmentioning
confidence: 95%
“…In this study, it was found that students with more increased age had significantly lower intention to get vaccinated. The most frequent reasons for students’ low intention to get vaccinated were their necessity for further research, unrevealed side effects of vaccines, and their opinion that vaccination was inefficient to limit the danger of infection [ 31 , 32 ]. Similarly, Shahwan et al [ 29 ] indicated that students had low confidence in COVID-19 vaccination and preferred vaccines to be domestically manufactured instead of imported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, medical and nursing students’ ability to volunteer in health-care assistant positions that can significantly benefit health-care systems during times of emergency has been demonstrated by experience with the current pandemic. 13 They are also at risk of COVID-19 during hospital training and clinical practice. Vaccinating students is also of high importance as they can use their personal expertise based on better knowledge to educate their relatives, friends in the neighborhood and the public regarding the vaccine.…”
Section: Introductionmentioning
confidence: 99%